Evaluation of Plastic Waste Management at Depo Koja, North Jakarta - Algafari Rizkyprima; Ananto Kusuma Seta; Desy Safitry (Indonesian Interdisciplinary Journal of Sharia Economics)
This research aims to analyze the evaluation of plastic waste management policy at Depo Koja, North Jakarta. Based on the results of the study, it can be concluded that the goal of realizing a healthy and clean community environment from plastic waste from the plastic waste management policy at the Koja Waste Depot, North Jakarta, is in accordance with that put forward by the policy manager. The problem with this plastic waste management policy is the lack of public awareness in helping to manage plastic waste, and many people still litter. The standardization of activities from this plastic waste management policy is reduce, reuse, and recycle. Where officers collect waste from the community, then sort out which waste can still be used, and there is also waste that is then recycled. Then, for the level of change that occurs from plastic waste management at the Koja Waste Depot, North Jakarta, it has improved and has a high commitment to waste management. The changes observed are the result of these activities or due to other causes in waste management. In Koja, North Jakarta Waste Storage Depot is a change occurs because there is a commitment relationship in plastic waste management. The management of plastic waste at the Koja Waste Depot, North Jakarta, is felt by the community by reducing the sight of piled up garbage and unpleasant odors, as well as the utilization of plastic waste to be made into other materials or recycled at the Koja Waste Bank, North Jakarta.